Seeking Solitude: Glenn Gould and the Goldberg Variations - Innes, Dale (Canada Penumbra, 2015)
GLENN GOULDs legacy continues to intrigue us; new areas of research emerge every year. In this study, Dale Innes explores the evolution of Glenn Goulds interpretation of the keyboard music of J.S. Bach, with particular emphasis on the contrast between his youthful 1955 recording of the Goldberg Variations and his final 1981 recording of the same work. This style transformation is placed in the context of Goulds life, including his early studies with Alberto Guerrero at the Toronto Conservatory of Music (now called the Royal Conservatory of Music), his abandonment of the concert stage to focus exclusively on recording, and some aesthetic directions that he was following later in life. The core of the study, an in-depth analysis of the two recordings of the Variations, leads the reader to a critical look at authenticity in the performance of Baroque music, and its reception by listeners. Innes concludes with a look at some writers who may have influenced Gould, including the Japanese author Natsume Soseki, and explores the special relationship that Gould developed with the Canadian North, particularly the area around Wawa Ontario on the east coast of Lake Superior.
Keywords: Bach, Johann Sebastian -- 1685-1750; 20th Century (1901-2000); Keyboard music; Piano; Goldberg Variations; Musical interpretation